A matter of value: assessing the scope and effects of Tanzania's national housing corporation's development strategy on Dar es Salaam's urban neighbourhoods. (1st January 2021) - Izar, Priscila; Mtwangi Limbumba, Tatu
ABSTRACT: Since the 1990s, the Tanzanian public housing authority, the National Housing Corporation (NHC), has been changing its goal, from prioritizing delivery of affordable housing, to becoming a leading commercial and residential real estate developer. This happens against a backdrop of market-based reform and the state's growing reliance on private markets to support urban development. In this paper, we look at the impact of NHC's new approach and its effect on housing production and every day practice in Dar es Salaam. The analysis is based on a case study of two new NHC middle to high-income development projects and housing practice in the neighbourhoods surrounding these projects. Analysis is informed by semi-structured interviews, and project and site investigation. Findings indicate that currently, NHC operates like a private corporation, prioritizing market-rate developments over low-income housing projects, and promoting segregated developments based on land value criteria, while also lacking protocols regarding its trickling down approach. High input costs and declining state subsidies are some of the factors mentioned as a challenge towards meeting the housing needs of moderate to low-income households. The paper contributes to the international debate concerning the state's adoption of business-like approaches to housing production and the affordability crisis.